2018
DOI: 10.21294/1814-4861-2018-17-3-34-40
|View full text |Cite
|
Sign up to set email alerts
|

Combined Modality Treatment for Patients With Inoperable Colorecral Liver Metastases

Abstract: The purpose of the study was to improve treatment outcomes for patients with inoperable colorectal liver metastases using the  combination of chemoembilization of the hepatic artery and radiofrequency ablation.Material and methods. Treatment outcomes of 60 patients with methachronic unresectable liver metastases from colorectal cancer  were analyzed. Eligibility criteria were as follows: absence of  extrahepatic metastases, size of metastases from 3 to 5 cm, and  inability to perform resection. All patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Hyperthermia in combination with RT and ChT is widely used in Europe, the United States, Japan, China, Russia, and other countries for the treatment of different tumor types and sites: mammary gland, prostate gland, lung, liver, intestinal tract, bonny tissue, glioblastoma, etc. [9][10][11][12][13][14][15][16][17][18][19][20][21]. Preclinical in vitro and in vivo studies have shown two aspects of cancer inhibition by combining HT with RT and ChT: the death of individual cells from hyperthermia and enhancing the effects of RT and ChT [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperthermia in combination with RT and ChT is widely used in Europe, the United States, Japan, China, Russia, and other countries for the treatment of different tumor types and sites: mammary gland, prostate gland, lung, liver, intestinal tract, bonny tissue, glioblastoma, etc. [9][10][11][12][13][14][15][16][17][18][19][20][21]. Preclinical in vitro and in vivo studies have shown two aspects of cancer inhibition by combining HT with RT and ChT: the death of individual cells from hyperthermia and enhancing the effects of RT and ChT [15].…”
Section: Introductionmentioning
confidence: 99%
“…The additional benefit of HT in combination with RT and ChT has been shown in a number of randomized clinical trials. Thus, for example, the overall response rate increased from 38% to 60% for patients with breast cancer who received HT + RT, while the treatment of cervical cancer at stage IIB-III-IVA with a combination of RT, ChT, and HT showed improved complete response rates and significantly increased overall survival [16,17]. Combining these methods has also proven to be effective in the preoperative treatment of stage III lung cancer [19].…”
Section: Introductionmentioning
confidence: 99%
“…мутация в этом гене возникает на ранних этапах канцерогенеза [5], участвует в активации раковых стволовых клеток [12] и связана с более быстрым и агрессивным метастазированием [13]. Кроме того, её наличие указывает на невозможность применения таргетных анти-EGFR препаратов [11], используемых при лечении метастатического колоректального рака, который выявляют у каждого третьего пациента на момент постановки диагноза [16]. *-8 издание классификации TNM злокачественных новообразований [7] Определение мутационного статуса опухоли образцы нефиксированной опухолевой ткани были взяты под контролем врача-патоморфолога в короткое время после резекции кишки (не более 30 мин).…”
unclassified